PERSEPSI SISWA SMK KRISTEN (TI) SALATIGA TENTANG BAHAYA MEROKOK BAGI KESEHATAN (Department of Physical Education, Sport, Health and Recreation, 2015)
There are 54 % tenth grade students of SMK Kristen (TI) who smoke, whereas there are some counseling and information about the danger of smoking were given and the rule about smoking prohibition has been applied. Seeing the data, it was needed to be investigated, about how the students’ knowledge and perception on the danger of smoking for health is. This survey research was in the academic year of 2012-2013 using sampling total of 102 students of tenth graders of SMK Kristen (TI) Salatiga. The data about the students’ knowledge and perception about the danger of smoking was taken from the questionnaire and was supported through an interview to the Guidance and Counseling teacher and the Sports teacher. The data was analyzed using bivariate analysis using chi quadrate test. The result of the study shows that the students have big knowledge about the danger of smoking for their health. Therefore, all of the efforts above totally can lead the students into positive activities and guide the students into an independent person and aware of the body and soul health.